Peningkatan Kinerja Kader Posyandu Desa Cogreg Kabupaten Bogor melalui Sistem Informasi Pelayanan Posyandu (SIPANDU) Berbasis Web - Dinar Ajeng Kristiyanti; Deli Novera; Nila Anjani; Nia Tania; Finanita Andini; Nasrulloh Nasrulloh (Jurnal Pengabdian Pada Masyarakat, 2021)
PERFORMANCE IMPROVEMENT OF POSYANDU CADRES IN COGREG VILLAGE, BOGOR REGENCY THROUGH THE WEB-BASED POSYANDU SERVICE INFORMATION SYSTEM (SIPANDU). Integrated service post (Posyandu) located in Parung District, Bogor Regency is one of the community health services, especially for toddlers and pregnant women, which are run by women around the environment or sometimes called cadres and bidandesa. Currently, services at Posyandu Village Cogreg Bogor Regency do not yet have an information system, it is still done manually, which means that technology has not been touched at all. Starting from the activity of recording the posyandu participant data until the recapitulation of posyandu data and the lack of target information for notification of posyandu schedules, so that it is time efficient and makes data collection in posyandu cadres. Therefore, to overcome the problems that exist in Posyandu Desa Cogreg Bogor Regency, it is necessary to develop a Posyandu Service Information System (SIPANDU) in Cogreg Village, Bogor Regency. The research stages start with the planning stage, namely location surveys and cadre interviews, the preparation stage, namely preparing resources to be used such as system design, website creation and training for posyandu cadres. implementation, namely the application of the SIPANDU website, and the last stage of the evaluation, which is seen from the success rate of the application in optimizing the performance of posyandu cadres and cadre skills in running the SIPANDU website. The result of the research is the creation of a Web-based Posyandu Information System (SIPANDU) website at Cogreg Village, Bogor Regency which was built using php language and based on a questionnaire that has been distributed to posyandu cadres and participants as respondents, it shows that with this website cadres and residents are helped in optimizing the performance of the posyandu system. in the village of Cogreg, Bogor Regency.